Integrasi Sains dan Agama: Sebuah Tawaran dari Ken Wilber untuk Zaman Ini - Lumban Gaol, Efron (MELINTAS An International Journal of Philosophy and Religion (MIJPR), 2012)
Religion has been an institution that plays a leading role in matters of human religious and spiritual life. One might ask whether in the last centuries religion still did its job to encourage human beings to seek the religious truths and whether it still prevented them from the fall into negative tendencies. Did not religion tend to be one of the stimulants to radicalism, fundamentalism, and terrorism, even in the areas that were regarded as the origin of religiosity and religions? If so, what was left of religion? For Ken Wilber, there is only one major element in religion that can make religion play the leading role in the midst of confusion and change in this age, that is, contemplation. Contemplation leads human beings to face the Absolute. In this contemplation religion needs to be correlated with science by juxtaposing and exploring the knowledge from both fields and by analysing the five correlative attitudes. This effort is a kind of reframing process to create a map of existence which enables us to fulfil the three strands of valid knowing to verify the whole knowledge.